Hubungan Tingkat Pendidikan Terhadap Tingkat Pengetahuan Masyarakat Tentang Pengobatan Hipertensi Di Dusun Grojogan Wirokerten Banguntapan Bantul - Hastuti, Dwi; Habibah, Khifdiana Rifqi (PHARMANAJA : PHARMACEUTICAL JOURNAL OF UNAJA, 2022)
Abstract Background: The prevalence of hypertension has increased according to Riskesdas 2018 data from 25.8% to 34.1%. Data on the health profile of Bantul Regency in 2020, hypertension ranks first out of the top 10 diseases at the Bantul Regency Health Center with a total of 83,932 cases. From some research results show the level of education can increase knowledge about health. Objective: To determine the relationship between education level and community knowledge level about hypertension treatment in Grojogan Wirokerten Village Banguntapan Bantul January 2022 Method: The type of research used is analytic observational with a cross sectional approach. Sampling with purposive sampling technique. The number was calculated using the Slovin formula as many as 96 respondents. The instrument used in this study was a questionnaire, the results of the answers from the questionnaires were assessed after the data was processed and then analyzed using SPSS with kruskal-walls test Results: The results showed that there were 43 respondents with good knowledge (44.80%) and 30 respondents (31.25%) enough, and 23 respondents (23.95%) less. The results of data processing from the kruskal-walls test obtained the Asymp.Sig (2-tailed) value of 0.000 <0.05, which means Ha is accepted, meaning that there is a significant relationship between the level of education and the level of community knowledge Conclusion: There is a relationship between the level of education and the level of public knowledge about the treatment of hypertension